2021
DOI: 10.1038/s41598-021-85743-z
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of distant organs by tumor cells generating circulating homotypic clusters adaptive to fluid shear stress

Abstract: Once disseminated tumor cells (DTCs) arrive at a metastatic organ, they remain there, latent, and become seeds of metastasis. However, the clonal composition of DTCs in a latent state remains unclear. Here, we applied high-resolution DNA barcode tracking to a mouse model that recapitulated the metastatic dormancy of head and neck squamous cell carcinoma (HNSCC). We found that clones abundantly circulated peripheral blood dominated DTCs. Through analyses of multiple barcoded clonal lines, we identified specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Both P2Y2 receptors ablation and ATP release blockade strongly reduce metastasis (Schumacher et al, 2013). Another known interaction occurs between a6b1-integrin on platelets and ADAM9 on CTCs (Mammadova-Bach et al, 2016). A different advantage of CTCs binding platelets is the activation of YAP1 signaling reducing anoikis (Haemmerle et al, 2017).…”
Section: Looking For Allies : Interaction Of Ctcs With Other Blood Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both P2Y2 receptors ablation and ATP release blockade strongly reduce metastasis (Schumacher et al, 2013). Another known interaction occurs between a6b1-integrin on platelets and ADAM9 on CTCs (Mammadova-Bach et al, 2016). A different advantage of CTCs binding platelets is the activation of YAP1 signaling reducing anoikis (Haemmerle et al, 2017).…”
Section: Looking For Allies : Interaction Of Ctcs With Other Blood Co...mentioning
confidence: 99%
“…Similarly, CTC clusters under FSS develop their own survival strategies like the generation of stable cell aggregates resistant to anoikis in an E-cadherin-dependent manner. Interestingly, CTCs clusters are also able to regulate their cortical actin-myosin dynamic achieving higher stability under FSS (Maeshiro et al, 2021). Hetero-cluster formed between CTCs and CAFs enhance FSS resistance via intercellular contact and soluble derived factors.…”
Section: Mechanoadaptation : Ctcs Force Their Way To Metastasismentioning
confidence: 99%
“…This form of deformation of the member is known as shear, and its cross section is the shear surface. The magnitude of the shear force per unit area of the cross section is called shear stress Blood flow and peripheral cells ( Maeshiro et al., 2021 ; Pomianek et al., 1996 ) Strain Describes the deformation of an object relative to its original length, measured as a percentage Solid tumor; intravascular wall ( Cardillo et al., 2006 ) Stiffness Describes the elasticity of a material or the recovery of its original shape after deformation Solid tumors; fibroblasts; extracellular matrix ( Seewaldt 2014 ; Fenner et al., 2014 ; McLane and Ligon 2015 ) Flexibility Describes the ability of an object to recover its original shape after the removal of an external force. Solid tumors; intravascular walls; extracellular matrix ( Szabo and Merks 2013 ) Viscoelasticity Objects exhibit both elastic and viscous properties when they deformed.…”
Section: Biomechanics On Tumor Cells During Immune Escapementioning
confidence: 99%
“…Their presence is generally associated with bad prognosis [4] and several factors are thought to contribute to the increased metastatic potential of CTC clusters compared to single CTCs. For instance, while in circulation, CTC clusters might have increased resistance to shear stress [16], programmed cell death, anoikis [17], immune attacks [18] and drug therapies [19]. Furthermore, it has been shown that CTC clusters feature DNA methylation patterns that promote the expression of stem-cell related genes [20], and that the formation of clusters promotes a metabolic switch that increases the efficiency of metastasis [21].…”
Section: Introductionmentioning
confidence: 99%